Determining Factors for Parents to Choose a School: Empirical Analysis of Religious Based Private Schools - Jonathan, Steve Arthur; Rantung, Priccilya Lidya Regina; Mandagi, Deske W. (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This study explores the factors influencing parental decision-making in choosing a school in the context of private, faith-based education. Using a quantitative descriptive and exploratory approach, this research investigates various factors shaping parents' interest in choosing a school. The population examined were parents of students attending private Christian schools, resulting in a purposive sample of 235 respondents. The sampling technique targets parents actively involved in the school community and has varying levels of involvement and perspectives on the school selection process. Data was collected through an online survey conducted between June and September 2023. Next, Confirmatory Factor Analysis (CFA) using SmartPLS was used for data analysis. This study identified eight factors influencing parental decision-making: teacher ability, school location, religious values, school facilities, school image, perceived costs, school environment, and school safety. The implications of these findings highlight the school's strategy to increase its attractiveness, thereby increasing school enrollment rates.